Eksplorasi Etnofisika pada Tenun Ikat ”Hinggi Kaworu” Masyarakat Kabupaten Sumba Timur - Yulita Adelfin Lede; Geterudis Kerans; Oktavianus Deke; Yohanes Engge (Kappa Journal, 2025)
This study aims to analyze the concepts of physics found in the process of making hinggi kaworu ikat weaving. Hinggi Kaworu is a type of ikat weaving originating from Sumba Island in East Nusa Tenggara. This study uses a qualitative descriptive research method with an ethnophysical approach conducted in Prailiu Village, East Sumba Regency. Data was obtained from eight (8) weavers through observation, interviews, and documentation. The instruments used in this study were observation sheets, interview sheets, and documentation. Data analysis included data reduction, data presentation, and conclusion drawing. The results of the study show that the ikat weaving process consists of 11 stages, namely: 1) Pahulur; 2) Kabukul; 3) Pamening; 4) Karandi; 5) Hondu; 6) Ngiling; 7) Katahu; 8) Walahu; 9) Pameirang; 10) Pawunang; and 11) Kabakil. The main concepts identified include: 1) The principle of moment of force in the yarn winding process, 2) Tension in yarn unwinding, which affects the strength of the fabric, 3) Jurin's Law in the fabric dyeing process, 4) Pressure and Newton's Law in the cutting process.